Aktualisasi Karakter Kristus Menurut Philip Yancey Bagi Pendidikan Iman Kristen - Nggebu, Sostenis; Mardiani, Ridha (Didache: Journal of Christian Education, 2023)
The problem of this article is discussing the importance of Philip Yancey's Christological views applied in efforts to educate Christians in their faith which is centred on Christ. The purpose of this article is to explain Yancey's thoughts about the figure of Jesus who changes the lives of believers to become like Him. The method used is literature study. The results show that Yancey's thoughts about the characteristics of Jesus were not to stimulate objective academic-dogmatic thinking, but rather to present personal reflections as a journalist in order to reveal the identity of the Nazarene Youth through the literature he wrote. The Jesus he knew was a figure who changed him and would also change every person who met personally with the Son of God. Yancey tries to develop a new synthesis regarding the character and profile of Jesus and encourages readers to welcome Jesus as the authority over human life. Yancey's ideas about the figure of Jesus can be used as material for Christian faith education for the maturation of believers' faith. In conclusion, people who know and believe in Jesus personally are guaranteed to experience renewal of life and become like Him.